The Impact of Board Size and Independent Directors on NPL Ratios: A Comparative Analysis of OLS and Quantile Regression Methods - Audrey Prajna; Regi Muzio Ponziani (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This research aims to examine the effect of board size, independent directors, big 4 auditors, audit committee size, audit committee expertise, and market concentration on NPL ratio. The data were taken from banks listed on Indonesian Stock Exchange from 2018-2022. There are two methods applied, multiple regression using ordinary least square (OLS) and quantile regression. The results show that board size and independent directors affect NPL ratio. Control variables, namely capital adequacy ratio and bank size, also affects NPL ratio. Multiple regression, however, fails to detect the influence of independent directors. It also exaggerates the effect of capital adequacy ratio and revenue diversification on NPL ratio. In the presence of nonnormality and heteroscedasticity, this research recommends the use of quantile regression to overcome the weakness of multiple regression using OLS. These findings provide important theoretical and practical implications. Theoretically, this study contributes to the corporate governance and banking risk literature by demonstrating that governance mechanisms, particularly board size and independent directors, play a significant role in influencing credit risk. Methodologically, the study highlights the superiority of quantile regression over OLS when dealing with non-normal and heteroscedastic data, thereby improving the reliability of empirical findings. Practically, bank management should pay greater attention to the composition and effectiveness of boards, especially by strengthening the role of independent directors to improve credit risk oversight and reduce NPL ratios. Regulators may also consider encouraging stronger governance practices and adopting more robust analytical approaches in evaluating banking performance and risk management.